STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN SEKOLAH SMKN 2 REJANG LEBONG - Dianto, Aris; Yanto, Ari; Bastian, Dian; Kurniawan, M. Efrry; Harahap, Emmi Kholilah; Hamengkubuwono (Department of Islamic Education Management, 2023)
One of the most decisive factors in the success of development in schools is the principal's strategy. A description of the principal's strategy for planning, implementing, and supervising quality improvement is the goal of this study. A qualitative approach is implemented in this study, while the method used is descriptive method. Observations, interviews, and documentation studies are used as a means of collecting data. Principals, educators, students, and school committees are the subjects of this research activity. Based on the research findings, the researcher leads to interesting conclusions: 1) The strategy adopted by the principal in the field of quality improvement planning is that all parties in the school are involved in the planning carried out by the principal, also giving teachers the opportunity to carry out quality planning, budgeting schools in collaboration with school committees; 2) As part of the school principal's approach/strategy in efforts to improve quality, namely teacher qualifications in the process of carrying out learning must be appropriate, carrying out the learning process according to the curriculum, and providing assistance to teachers in carrying out learning evaluations; 3) Supervision of teaching by applying group techniques and individual techniques to efforts to improve quality in schools is the principal's strategy in supervising quality improvement.